2003
DOI: 10.1002/cncr.11209
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometry and quantitative immunohistochemical study of cell cycle regulation proteins in invasive breast carcinoma

Abstract: BACKGROUNDBetween January 11, 1991 and January 8, 1992, 104 patients with previously untreated, invasive, primitive breast carcinoma were admitted to the authors' hospital.METHODSFor each patient, flow cytometry DNA analyses on frozen samples and on immunohistochemical staining were performed, including Ki‐67, cyclin A, p53, and p21waf1 (p21), with assessment of the percentages of positive nuclei were assessed. Correlations with classic clinicopathologic data and survival (overall, metastasis free, or recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
25
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 103 publications
6
25
0
1
Order By: Relevance
“…We found a strong correlation between cyclin A, mitotic count, tumour grade and Ki-67, which is in line with previous studies in breast cancer (Michalides et al, 2002;Michels et al, 2002). Cyclin A was the only marker that showed a statistically significant correlation to both TFR and OS; therefore, it seems to be the most useful marker of proliferation.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found a strong correlation between cyclin A, mitotic count, tumour grade and Ki-67, which is in line with previous studies in breast cancer (Michalides et al, 2002;Michels et al, 2002). Cyclin A was the only marker that showed a statistically significant correlation to both TFR and OS; therefore, it seems to be the most useful marker of proliferation.…”
Section: Discussionsupporting
confidence: 91%
“…We used a cutoff value of 10.5% for the high and low cyclin A positivity groups. This is in line with three other studies, where median values varying between 8 and 11% have been used (Michalides et al, 2002;Michels et al, 2002;Kuhling et al, 2003;Rudolph et al, 2003). In the fourth study, four different categories were used for cyclin A positivity and the median category was between 15 and 30% (Bukholm et al, 2001).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…HR associated with Ki-67 positivity in this case) from studies with inherent dissimilarities. The observed disparity among the conclusions of different studies, responsible for the observed heterogeneity, can be quantified by applying Bukholm et al (2003) 147 No Ceccarelli et al (2000) 217 Yes Galiegue et al (2004) 117 No Gasparini et al (1992) 164 Yes Haerslev et al (1996) 487 Yes Jalava et al (2000) 414 No Kroger et al (2006) 157 No Kronblad et al (2006) 377 Yes Lampe et al (1998) 142 Yes Liu et al (2000) 225 Yes Michels et al (2003) 104 No Molino et al (1997) 322 Yes Rudas et al (1994) 184 No Tsutsui et al (2005) 249 Yes Yang et al (2003) 147 No…”
Section: Discussionmentioning
confidence: 99%